The features of norms formed in constructing student-generated drawings to explain physics phenomena - Chang, Jina; Park, Joonhyeong; Tang, Kok-Sing; Treagust, David; Won, Mihye (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Student-generated drawing is a useful strategy to construct students’ scientific ideas. For exploring ways to support student-generated drawing, we focused on the perspective of ‘Norms’–shared behaviour patterns desirable in a community. We investigated what norms were formed and how they emerged when students made drawings to explain phenomena. Data were collected from classroom observations, interviews and students’ artefacts from five physics lessons in a primary school gifted programme. The data were analysed based on three essential features of norms: justifiability, sharing and behaviours. Consequently, two main norms were reported with four sub-norms in terms of two processes of drawing: meaning-making and representing. First, to show invisible mechanism, ‘explaining why’ was emphasised as a main norm of the meaning-making process. This norm was shared in classroom discussions and drawings by interacting with two sub-norms that supported students to interpret phenomena with ‘key concepts’ at a ‘particle level’. Second, ‘telling a story visually’ was another main norm of the representing process. This norm was formed with two sub-norms that encouraged students to visualise ideas with ‘their own symbols’ in ways that were ‘easy to understand’. These results indicate that norms can guide desirable directions for students to construct and visualise ideas.